Variação nas metodologias de análise de germinação e vigor em sementes de arroz e soja - Fernandes, Tiéle Stuker (2015)
The objective of this study was to identify variation in the results of germination and vigor in rice seeds and soybeans due to the different methodologies used in the test driving. Rice cultivars seeds were analyzed Guri Inta CL and Puitá Inta CL and soybean cultivars Nidera RG 5909 and BMX Tornado RR, and used four lots of each cultivar. Initially the seeds were characterized as their physical, physiological and health and were subsequently subjected to the following experiments: 1) Proportion of distilled water used to moisten the paper germination; 2) pH of distilled water; 3) Wash the germination paper; 4) Number of seeds in each sub-repeat testing; 5) use of germination rolls or pancakes; and 6) Weight of the germination paper. The experiments were conducted in a completely randomized design and were evaluated by tests: germination, first count of germination, germination speed index, shoot length of seedlings, main root length and dry mass of seedlings. The rice germination test, carried out by routine laboratories, should be conducted according to the recommendations of the Rules for Seed Analysis, because none of the variations in methodologies analyzed interfere with the results of this test. The number of seeds in each sub-repetition interfere with the results of the germination of both soybean cultivars. Thus, the germination test of soybean cultivars should be conducted with 50 seeds in each sub-repetition and following the other recommendations of the Rules for Seed Analysis. It is recommended that the effect of both tests studied rice cultivars are conducted with the ratio of water to moisten the paper germination between 2.0 and 3.0 times the mass of dry paper, distilled water of pH between 4.0 and 5.0, with paper subjected to three washes in distilled water and with four replications of 100 seeds. The vigor tests of soybean cultivars studied must be conducted with the proportion of distilled water from 2.0 to 3.0 times the mass of dry paper with distilled water of pH between 5.0 and 6.0, with eight sub -repetições of 50 seeds and the form of rolls.